Zenker Diverticulum: Does Size Correlate with Preoperative Symptoms? - Martinez-Paredes, Jhon F.; Alfakir, Razan; Kasperbauer, Jan L.; Rutt, Amy (International Archives of Otorhinolaryngology, 2021)
Introduction Zenker diverticulum (ZD) usually affects adults after the 7th decade of life. Treatment for ZD is indicated for all symptomatic patients, but some patients prefer to defer surgical treatment until symptoms get worse and decrease their quality of life.Objective To evaluate the association of the preoperative symptoms in ZD patients with the size of the ZD.Methods A retrospective study design. Electronic medical records were used to identify patients diagnosed with ZD and treated over 11 years. Data collection included the chief complaints and symptoms, medical history, and findings on radiologic swallow evaluations of the patients. The diverticulum size was stratified into 3 groups: small (< 1 cm), moderate (1–3 cm), and large (> 3 cm).Results A total of 165 patients were enrolled and stratified by diverticulum size (48 small, 67 medium, and 50 large). Dysphagia, cough, and regurgitation were the most prevalent symptoms. Dysphonia was more frequent among patients with a small pouch. Logistic regression analysis showed that dysphagia and choking were associated with large and medium diverticulum size (p < 0.05). Additionally, dysphonia was significantly associated with the presence of a small-sized ZD (p < 0.04).Conclusion Upper gastrointestinal symptoms such as dysphagia and choking may be associated with a ZD > 1 cm and should always be evaluated. Additionally, the presence of dysphonia was found to be correlated with a ZD < 1 cm, suggesting that a prompt and appropriate fluoroscopic evaluation must be considered in those patients in whom no other clear cause of dysphonia is evident.
Keywords: zenker diverticulum; pharyngeal pouch; esophageal diverticulum; dysphagia; dysphonia